Multi-color carrier-envelope-phase stabilization for high-repetition-rate multi-pulse coherent synthesis - McCracken, Richard A; Gianani, Ilaria; Wyatt, Adam S; Reid, Derryck T (Optics letters, 2015)
Using a zero-offset carrier-envelope locking technique, we have synthesized an octave-spanning composite frequency comb exhibiting 132-attosecond timing jitter between the constituent pulses over a one-second observation window. In the frequency domain, this composite comb has a modal structure and coherence which are indistinguishable from those of a comb that might be produced by a hypothetical single mode locked oscillator of equivalent bandwidth. The associated phase stability enables the participating multi-color pulse sequences to be coherently combined, representing an example of multi-pulse synthesis using a femtosecond oscillator.